Storm child ebook - Robotham, Michael (Cyrus Haven, 2024)
"No one does suspense better." —Stephen King Cyrus Haven and Evie Cormac return in this "razor-sharp and emotionally charged" (Lisa Gardner) psychological thriller, which finally unlocks the secrets of Evie's past. The mystery of Evie Cormac's background has followed her into adulthood. As a child, she was discovered hiding in a secret room where a man had been tortured to death. Many of her captors and abusers escaped justice, unseen but not forgotten. Now, on a hot summer's day, the past drags Evie back as she watches the bodies of seventeen migrants wash up on a Lincolnshire beach. There is only one survivor, a teenage boy, who tells police their small boat was deliberately rammed and sunk. Psychologist Cyrus Haven is recruited by the police to investigate the murders—but he recognizes immediately that Evie has some link to the tragedy. By solving this crime, he could finally unlock the secrets of her past. But what dark forces will he set loose? And who will pay the price? "Well paced with a slow tension building to a gripping climax [and] a very pleasing ending, Storm Child is a terrific addition to the series. Although this could be enjoyed as a stand-alone" (Mystery and Suspense Magazine ).